The relationship between consumer confidence indices and economic & financial variables - an econometric analysis with country comparisons - Aktaş, Hilal (My University, 2011)
THE RELATIONSHIP BETWEEN CONSUMER CONFIDENCE INDICES AND ECONOMIC, FINANCIAL VARIABLES – AN ECONOMETRIC ANALYSIS WITH COUNTRY COMPARISONS The primary objective of this study is to examine the relationship between economic indicators that affect the financial markets and consumer confidence index. This study takes both theoretical and empirical approach to study the relationship between economic indicators and consumer confidence index. Many researchers are interested in the relationship between economic indicators and consumer confidence index. Some studies advocate that there is no significant correlation between economic indicators and consumer confidence index. On the other hand, some studies support the strong correlation between the economic variables and consumer confidence index. Undoubtedly, economic indicators as inflation rates, unemployment rates, and exchange rates are one of the most important factors that shape the investment decisions for the household consumption. The direction of the relationship between economic indicators and CCI performances depends on the time period, global economic environment, the structure of the economy and stock market of the country. Before analyzing the consumer confidence index, important economic indicators affecting the consumer confidence index, are described. Theories related with economic variables are elaborated. Basic common characteristics of consumer confidence are analyzed by using panel data analysis. The economic situation of analyzed consumer confidence is emphasized. The data of Italy, USA, UK, Turkey, Japan, and Canada are selected. In the final section, panel data analysis is performed in order to show the relationship between economic indicators that have impact on financial and consumer confidence performances understand. The results obtained from performing panel data analysis enable us to know which economic indicators move together with the performance of the consumer confidence and there is a correlation among the Consumer Confidence Index, Unemployment Rates and Inflation Rates.

TÜKETİCİ GÜVEN İNDİSİ İLE EKONOMİK & FİNANSAL VERİLER ARASIDAKİ İLİŞKİ - ÜLKELERARASI KARŞILAŞTIRMALI EKONOMETRİK ANALİZ Bu çalışmanın temel amacı finansal piyasaları etkileyen ekonomik göstergeler ve tüketici güven endeksi arasındaki ilişkiyi incelemektir. Bu çalışma ekonomik göstergeler ve tüketici güven endeksi arasındaki ilişkiyi incelemek için hem teorik hem de ampirik bir yaklaşım getirmektedir. Birçok araştırmacı ekonomik göstergeler ve tüketici güven endeksi arasındaki ilişki ile ilgilenmiştir. Bazı çalışmalarda ekonomik göstergeleri ve tüketici güven endeksi arasında anlamlı bir ilişki olduğunu savunulmuş bazılarında ise ekonomik değişkenler ve tüketici güven endeksi arasında güçlü bir korelasyon bulunmuştur. Kuşkusuz, enflasyon oranları, işsizlik oranları, döviz kurları gibi ekonomik göstergeler hanehalkı için tüketim ve yatırım kararlarında önemli faktörlerden biridir Ekonomik göstergeler ve CCI performansları arasındaki ilişkinin yönü zamana, küresel ekonomik ortam, ülkenin ekonomi ve borsa yapısına bağlıdır. Bu çalışmada tüketici güven endeksi analiz edilmeden önce, tüketici güven endeksi etkileyen önemli ekonomik göstergeler açıklanmıştır. Öncelikle ekonomik değişkenler ile ilgili teorileri işlenecek ardından tüketici güven temel ortak özellikleri panel veri analizi kullanılarak analiz edilecektir. Analiz için ise ABD, İngiltere, Türkiye, Japonya, Kanada verileri seçilmiştir. Son bölümde ise finansal piyasalar üzerinde etkisi olan ekonomik göstergeler ve tüketici güven performansları arasındaki ilişkiyi anlamak için panel veri analizi kullanılacaktır. Panel veri analizi ile elde edilen sonuçlar bize ekonomik göstergelerin tüketici güven endeksi performansı ile birlikte hareket ettiği sonucuna ulaştırmıştır. Statik model regresyon sonuçları Tüketici Güven Endeksi, İşsizlik Oranları ve Enflasyon Oranları arasında anlamlı bir ilişki olduğunu göstermektedir.
Keywords: Döviz; Enflasyon; İşsizlik; Tüketici Güven Endeksi